2019
DOI: 10.1136/bmj.l1495
|View full text |Cite
|
Sign up to set email alerts
|

Physical inactivity, cardiometabolic disease, and risk of dementia: an individual-participant meta-analysis

Abstract: ObjectiveTo examine whether physical inactivity is a risk factor for dementia, with attention to the role of cardiometabolic disease in this association and reverse causation bias that arises from changes in physical activity in the preclinical (prodromal) phase of dementia.DesignMeta-analysis of 19 prospective observational cohort studies.Data sourcesThe Individual-Participant-Data Meta-analysis in Working Populations Consortium, the Inter-University Consortium for Political and Social Research, and the UK Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
188
5
6

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 198 publications
(226 citation statements)
references
References 38 publications
5
188
5
6
Order By: Relevance
“…Given the increase in life expectancy, AD is increasingly a public health challenge and measures to prevent or delay the onset of dementia are urgently needed. However, in combination with previous literature [13,14], the present study provides little evidence that recommending physical activity would help to prevent AD. Table 1 Mendelian randomization estimates between accelerometer-based physical activity and Alzheimer's disease…”
Section: Discussioncontrasting
confidence: 41%
“…Given the increase in life expectancy, AD is increasingly a public health challenge and measures to prevent or delay the onset of dementia are urgently needed. However, in combination with previous literature [13,14], the present study provides little evidence that recommending physical activity would help to prevent AD. Table 1 Mendelian randomization estimates between accelerometer-based physical activity and Alzheimer's disease…”
Section: Discussioncontrasting
confidence: 41%
“…11 A recent meta-analysis of prospective studies, totalling 36 investigations and over three million subjects followed up for a median period of 12 years, concluded that achieving the WHO recommended physical activity levels was associated with 17% lower risk of cardiovascular events (relative risk (RR), 0.83; 95% confidence interval (CI), 0.77-0.89), 23% lower risk of cardiovascular mortality (RR, 0.77; 95% CI, 0.71-0.84) and 26% lower incidence of type 2 diabetes (RR, 0.74; 95% CI, 0.72-0.77). 12 These findings were more recently confirmed by Kivim€ aki and colleagues, 13 who pooled data from 19 prospective observational cohort studies, totalling 404,840 subjects. Overall, physical inactivity was associated with 24% higher risk of coronary heart disease (hazard ratio, 1.24; 95% CI, 1.13-1.36), 16% enhanced risk of stroke (hazard ratio, 1.16; 95% CI, 1.05-1.27) and 42% higher risk of diabetes (hazard ratio, 1.42; 95% CI, 1.25-1.61).…”
mentioning
confidence: 74%
“…The extent to which adults in the UK will revert back to their usual PA regimes once lockdown measures are relaxed is unclear, but the potential for multiple lockdowns being necessary over a protracted period could lead to prolonged periods of low PA in a substantial proportion of the population. This is concerning because it is well established that insufficient levels of PA are associated with poor mental [6] and physical [7,8] health and with premature mortality [9].…”
Section: Discussionmentioning
confidence: 99%